A pilot study on the effectiveness of peer-teaching as a method of providing dental health information to grades one and two children - Alcaraz, Elizabeth A.
This study aims to determine the effectiveness of peer-teaching as a means of providing dental health education to Grades One and Two children. Ninety-nine Grades One and Two pupils coming from two schools were involved. The children from one school was maintained as the control group while the children from the other school were used as the experimental group. From the experimental group, nine sixth graders were used as peer-teachers and were instructed on the dental health awareness program a few weeks before the study was undertaken on the Grades One and Two children. For the control group, dental health was instructed by dental students. Pre and post-tests were given before and after the implementation of the lessons to determine how much the children learned from the study. Likewise, pre and post-screenings (using the Greene and Vermillion method) were conducted to gauge the oral hygiene status of the children before and after they were taught. The results obtained states that the peer-teachers are indeed effective instructors of dental health education among the Grades One and Two children. Thus, it is with hope that a program such as this be implemented in primary schools in order that children be more aware of the importance of good dental health practices early in their growing years.